Cathepsin B cleavage of the trypsinogen activation peptide - Keim Volker; Bödeker Hans; Teich Niels (BMC Gastroenterology, 2002)
Abstract Background Cathepsin B is thought to play a central role in intrapancreatic trypsinogen activation and the onset of pancreatitis. A recent investigation of the cathepsin B mediated activability of wildtype trypsinogen and their mutations N29I, N29T and R122H, which are associated to hereditary pancreatitis, revealed no differences. This action seems to be restricted to the K23-I24 peptide bond, which is the trypsinogen activation bond. Here we investigated the influence of the mutations D22G and K23R of the trypsinogen activation peptide on the cleavability by cathepsin B. Methods To investigate the functional impact of the TAP mutations on cathepsin B mediated cleavage of the trypsinogen activating K23-I24 bond, the corresponding peptides pWT, APFDDDDKIVGG; pD22G, APFDDDGKIVGG; and pK23R, APFDDDDRIVGG were digested with cathepsin B for 30 min at pH 3.8 and 5.0, and the fragments were analysed by high-performance liquid chromatography. Results Without cathepsin B, less than 1 % of the peptides were hydrolysed. After a 30-minute digestion with cathepsin B at pH 5, 96% of pWT, 48% of pK23R, but only 2.4% of pD22G were hydrolysed. At pH 3.8, the cathepsin B cleavage of pWT and pK23R was less than at pH 5, whereas the cleavage of pD22G was completely inhibited Conclusions Cathepsin B mediated trypsinogen activation seems not to be a crucial pathogenic step in hereditary pancreatitis patients with the trypsinogen mutations D22G and K23R.